ISOLATION, IDENTIFICATATION, AND DETERMINATION OF THE ANTIBIOTIC SUSCEPTIBILITY PATTERN OF BACTERIA ASSOCIATED WITH DIABETIC FOOT ULCER - MWALIMU RAPHAEL JILANI; HAIDER HAMZHA BAAYWI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: This study involved isolating, identifying, and determining the susceptibility patterns of bacteria from diabetic patients who were hospitalized for diabetic foot ulcers. Methods: The specimen was collected using a deep swabbing approach from the feet of forty hospitalized patients with diabetes. The two sample swabs were delivered to the microbiology laboratory as soon as they were collected. One swab was used for microscopic examinations, and the other was utilized for culture. Three aseptically prepared agars – chocolate, MacConkey, and sheep blood were used for culture. In accordance with accepted clinical standards, the pathogens were identified. By performing the Kirby–Bauer disc diffusion method on Mueller–Hinton Agar medium, the isolates’ antibiotic sensitivity patterns were examined. Results: Twenty-five patients had microorganisms in their foot ulcers, whereas 15 patients had sterile samples (no pathological growth). Gram-negative (10) and positive (15) bacteria were recovered, with some patients having both types. Pseudomonas aeruginosa (32%), Klebsiella species (8%), and methicillin-resistant (10), sensitive (2), and coagulase-negative (3) strains of Staphylococcus aureus were identified. Conclusion: Imipenem was the antibiotic most sensitive to almost all of the isolates, whereas Penicillin G had more resistance to all of the isolates, and the other antibiotics had more variation. Our findings lead us to recommend that patients with diabetes be empirically given imipenem.